2022
DOI: 10.1002/adfm.202204068
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Self‐Standing Covalent Organic Frameworks toward Highly‐Efficient Nanofluidic Osmotic Energy Generator

Abstract: Nanofluidics is promising in the construction of highly-efficient osmotic energy generator, but it is still a challenge to develop large-scale and highperformance nanofluidic membranes. The emerging covalent organic frameworks (COFs) provide a desirable platform to create nanofluidic membranes with high ion selectivity and permeability towards effective osmotic energy conversion. Herein, an ultrathin self-standing COF nanofluidic membranes based on terephthalaldehyde-tetrakis(4-aminophenyl)methane is developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 43 publications
(55 reference statements)
0
22
0
Order By: Relevance
“…Covalent organic frameworks (COFs), a class of crystalline organic porous materials exhibiting permanent porosity and atomically ordered structures, have shown great potential for precise molecular/ion transport. The highly crystalline two-dimensional (2D) COF membranes have attracted particular attention for energy storage , and conversion , owing to the presence of ordered nanofluidic channels. We recently reported a highly crystalline and oriented COF membrane that offered an increased ion flux and output power density. , Jiang et al reported a COF membrane containing the highest charge density among all the reported nanoporous membranes .…”
mentioning
confidence: 99%
“…Covalent organic frameworks (COFs), a class of crystalline organic porous materials exhibiting permanent porosity and atomically ordered structures, have shown great potential for precise molecular/ion transport. The highly crystalline two-dimensional (2D) COF membranes have attracted particular attention for energy storage , and conversion , owing to the presence of ordered nanofluidic channels. We recently reported a highly crystalline and oriented COF membrane that offered an increased ion flux and output power density. , Jiang et al reported a COF membrane containing the highest charge density among all the reported nanoporous membranes .…”
mentioning
confidence: 99%
“…Recently, Wang et al constructed an ultrathin self-standing 1D COF nanofluidic membrane (denoted as BDA-TAM) having the ability to build an efficient nanofluidic osmotic energy generator. 29 As this, COF-based nanofluidic membrane, contains negative surface charges, it exhibits good selectivity towards cations and hence strong ionic conductance. Furthermore, the extraordinary stability of BDA-TAM extended across a wide range of saline solutions, temperatures, and pH values.…”
Section: Covalent Organic Frameworkmentioning
confidence: 95%
“…[1][2][3][4] Inspired by biological nanochannels, various biomimetic nanochannels have been constructed and used to regulate the transport behavior of ions in artificial systems. The design and application of materials based on biomimetic nanochannels have also been further developed, and promoted in the fields of gas separation, [5] water treatment, [6] osmotic energy harvesting, [7] and energy storage. [8] Membranes with nanochannel configures that modulate ion transport are known as nanofluidic membranes.…”
Section: Introductionmentioning
confidence: 99%